The complete chloroplast genome of weedy rice Oryza sativa f. spontanea - Chenfeng Dong; Yiyu Hu; Chuyu Ye; Longjiang Fan; Longbiao Guo (Mitochondrial DNA. Part B. Resources, 2021)
The emergence of weedy rice (Oryza sativa f. spontanea) has been considered as a serious global agricultural problem in recent decades. To better understand its speciation, here we assembled the complete chloroplast genome of O. sativa f. spontanea with the length of 134,502 bp. The assembly contains a large single-copy (LSC, 80,549 bp), a small single-copy (SSC, 12,347 bp) and a pair of inverted repeats (IRa and IRb, 20,803 bp each). A total of 132 unique genes were annotated, including 82 protein-coding genes, 42 tRNA genes and eight rRNA genes. Phylogenetic analysis showed that O. sativa f. spontanea (indica type) appears closely related to cultivated indica rice rather than wild rice, supporting the hypothesis that weedy rice originated from cultivated rice.